Do we need firm data to understand macroeconomic dynamics? - Michele Lenza; Ettore Savoia (Sveriges Riksbank, 2024)
We study the role of heterogeneity in the revenues of individual firms for euro area macroeconomic dynamics. To this end, we specify two models: a standard aggregate vector autoregressive model (VAR) and an "heterogeneous VAR" (HVAR). The VAR model includes only aggregate data, while the HVAR model also incorporates the feedback loop between firms' revenue distribution and aggregate variables. Our results demonstrate that the behavior of firms' revenue distribution plays a significant role in explaining the dynamics of key euro area macroeconomic variables.
Keywords: C11; C32; C52; C54; E22; E32; 330; Firm-level revenues; Functional Vector Autoregressions; Heterogeneous Agent Models; Business Cycle fluctuations